Cheap search, picky workers? Evidence from a field experiment - Harald Mayr (University of Zurich, Department of Economics, 2022)
Search frictions impede the labor market. Despite this indisputable fact, it is a priori unclear how job search costs affect search duration and unemployment: lower search costs make it easier to find a job, reducing search duration and unemployment, but may also increase the reservation wage, increasing search duration and unemployment. I collaborate with a recruiting company to directly test the effects of lower search costs in a field experiment among approximately 400 IT professionals in Switzerland. I find that workers are more likely to search for detailed job information, but not to file a job application, when search costs are lower. These findings are consistent with an increase in the reservation wage. Lower search costs might lead to picky workers, but fail to ultimately reduce search duration and unemployment.
Keywords: J63; J64; J24; M50; M54; 330; Job search; search costs; search frictions; recruiting; reservation wage